Computational Science and Its Applications -- ICCSA 2015 : 15th International Conference, Banff, AB, Canada, June 22-25, 2015, Proceedings, Part IV - Gervasi, Osvaldo; Murgante, Beniamino; Misra, Sanjay; Gavrilova, Marina L.; Rocha, Ana Maria Alves Coutinho; Torre, Carmelo; Taniar, David; Apduhan, Bernady O.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
The five-volume set LNCS 9155-9159 constitutes the refereed proceedings of the 15th International Conference on Computational Science and Its Applications, ICCSA 2015, held in Banff, AB, Canada, in June 2015. The 232 revised full papers presented in 22 workshops and a general track were carefully reviewed and selected from 780 initial submissions for inclusion in this volume. They cover various areas in computational science ranging from computational science technologies to specific areas of computational science such as computational geometry and security.
Agricultural and environment information and decision support systems -- Approaches or methods of security engineering -- Information systems and technologies for emergency preparedness and risk assessment -- Web-based learning -- Bio-inspired computing and applications -- Computer-aided modeling, simulation, and analysis -- Computational and applied statistics -- Computational geometry and security applications -- Computational algorithms and sustainable assessment -- Chemistry and materials sciences and technologies -- Computational optimization and applications -- Cities, technologies and planning -- Econometrics and multidimensional evaluation in the urban environment -- Future computing systems, technologies, and applications -- Geographical analysis, urban modeling, spatial statistics -- Land use monitoring for soil consumption reduction -- Mobile communications -- Mobile computing, sensing, and actuation for cyber physical systems -- Quantum mechanics: computational strategies and applications -- Scientific computing infrastructure -- Software engineering processes and applications -- Software quality -- Spatio-temporal analytics -- Virtual reality and its applications.
Keywords: Computer Communication Networks; Computer software; Software engineering; Computer simulation; Data mining; Computer Communication Networks; Algorithm Analysis and Problem Complexity; Software Engineering; Simulation and Modeling; Information Systems Applications (incl. Internet).; Data Mining and Knowledge Discovery